Social Media Education in Marketing Debog Banana Chips Products to She Yuha Snack MSMEs in Rengas Pulau Village, Marelan Medan - Sari, Revita; Muhammad, Idhamsyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The community service program was implemented in Rengas Pulau Village, Medan Marelan District, Medan City Regency targeting the local community. The program implemented with this target is an educational program on the importance of social media. With the targets and programs that have been designed, it is hoped that it will be able to increase understanding for MSME players. The aim of implementing this community service program is to solve various problems that exist in the She Yuha Snacks She Yuha Chips Debog Banana MSME which is the focus of the activity by utilizing social media. The method used in implementing this activity is the observation method, namely observing the problems in Rengas Pulau Island Village as the target of the activities to be carried out and documentation, namely documenting the photos or videos required for each activity.